PROFESIONALISME GURU PENDIDIKAN ANAK USIA DINI (PAUD) DALAM MENINGKATKAN MUTU PEMBELAJARAN DI LEMBAGA PAUD - Yossi Srianita; Azi Matur Rahmi (LPPM IAD Probolinggo, 2024)
Teacher professionalism is a key factor determining the quality of learning in Early Childhood Education (ECE) institutions. Professional teachers are expected to possess pedagogical, professional, personal, and social competencies that foster an effective, creative, and child-development-centered learning process. This study aims to analyze ECE teacher professionalism in enhancing learning quality, identify factors that support or hinder such professionalism, and describe efforts made to improve the quality of instruction. A qualitative approach with a descriptive method was employed. Data collection involved observation, interviews, and documentation, while data analysis encompassed data red uction, data presentation, and conclusion drawing. The results indicate that teacher professionalism positively influences learning quality, as evidenced by teachers' abilities to plan, implement, and evaluate instruction in alignment with children's developmental characteristics. Supporting factors include continuous training, institutional leadership support, and the availability of learning resources; conversely, inhibiting factors include limited facilities, restricted opportunities for competency development, and administrative burdens. Therefore, enhancing teacher professionalism through continuous training, mentoring, and competency development is a crucial step toward improving learning quality in ECE institutions.